Performance Measurement of Zakat Utilization: The Effectiveness of Zakat Distribution - Fadilah, Sri; Sundaya, Yuhka; Lestari, Rini; Rosdiana, Yuni; Maemunah, Mey; Ali, Azlan; K, Rashidah; Farhan J, Muhammad (KnE Social Sciences, 2023)
In this study, we will examine the performance of zakat. The background of the research is the zakat utilization program as one of the programs in the zakat intermediation role, performance must be assessed to see the sustainability of the program. One of them is the effectiveness of the zakat distribution program. The research method used is a case study of zakat programs (BAZNAS) in West Java area, with a descriptive analysis approach. Data collection techniques used were observation, in-depth interviews and documentation. The results of this study are expected to be an innovation that becomes a reference for zakat institution managers to assess the performance of zakat utilization by looking at the effectiveness of the zakat distribution program. Zakat distribution program at BAZNAS of West Java focuses on the economy, health, and education. BAZNAS of West Java is distributed for da’wah and the victims of natural disasters. Zakat utilization at BAZNAS of West Java covers the fields of economy, health, and education. In carrying out the role as a zakat distributor, BAZNAS of West Java still encounters obstacles that hinder the effectiveness of the zakat distribution program. Many measurements are used to assess the effectiveness of its role in zakat distribution, including the implementation of standard operating procedures (SOP). Keywords: effectiveness, zakat utilization, zakat